Stock Market Integration Among Asian Economies in a Case of India, China, and Japan - Bhullar, Pritpal Singh (International Research Journal of Business Studies, 2019)
Globalisation has opened the door for global investors to avoid the saturation of investment opportunities in the domestic market. Latest technological advancement, accessibility to financial and global information, liberalisation and globalisation put the global market into a new investment framework. The present paper aims to examine the level of cointegration between three big Asian economic powers India, China and Japan. Twenty-years data has been analyzed by applying Johansen Cointegration, Vector Error Correction Model, and other econometric statistical tests in E-Views. The findings suggest a long-run relationship between India (BSE) and Japan Stock indices (Nikkie), but no such integration find of these two stock indices with China Stock Exchange (Shanghai).